A Novel Approach Inducing Transplant Tolerance by Activated Invariant Natural Killer T Cells With Costimulatory Blockade. Issue 3 (6th February 2014) - Hirai, T.; Ishii, Y.; Ikemiyagi, M.; Fukuda, E.; Omoto, K.; Namiki, M.; Taniguchi, M.; Tanabe, K.
<x xml:space="preserve">Abstract</x> Invariant natural killer T (iNKT) cells are one of the innate lymphocytes that regulate immunity, although it is still elusive how iNKT cells should be manipulated for transplant tolerance. Here, we describe the potential of a novel approach using a ligand for iNKT cells and suboptimal dosage of antibody for CD40–CD40 ligand (L) blockade as a powerful method for mixed chimerism establishment after allogenic bone marrow transplantation in sublethally irradiated fully allo recipients. Mixed‐chimera mice accepted subsequent cardiac allografts in a donor‐specific manner. High amounts of type 2 helper T cytokines were detected right after iNKT cell activation, while subsequent interferon‐gamma production by NK cells was effectively inhibited by CD40/CD40L blockade. Tolerogenic components, such as CD11clowmPDCA1+ plasmacytoid dendritic cells and activated regulatory T cells (Tregs) expressing CD103, KLRG‐1 and PD‐1, were subsequently augmented. Those activating Tregs seem to be required for the establishment of chimerism because depletion of the Tregs 1 day before allogenic cell transfer resulted in a chimerism brake. These results collectively suggest that our new protocol makes it possible to induce donor‐specific tolerance by enhancement of the innate ability for immune tolerance in place of the conventional immunosuppression.